PUBLIC SPACES OF THE HOTELS IN THE CONTEXT OF CONTEMPORARY MEDIA CULTURE / ПУБЛИЧНЫЕ ПРОСТРАНСТВА ОТЕЛЕЙ В КОНТЕКСТЕ СОВРЕМЕННОЙ МЕДИАКУЛЬТУРЫ - SKRIPOVA T.V. / СКРИПОВА Т.В. (Наука телевидения, 2017)
Analyzing the dominance of media culture in the modern world on the example of the public space of a modern hotel, the author comes to the conclusion that the renovation and active use of public space in modern hotels characterize the mentality of the society of leisure and consumption as totally dependent on screen culture and vivid impressions. Media culture, permeating all public areas of the hotel, synthesizes them in the uninterrupted cultural continuum, the semantics of which is lined with numerous gadgets and screens.